(untitled) (Journal of Philosophy, Culture and Political Science, 2024)
The study of ethnic minority issues in Kazakhstan through the lens of modern philosophy and existentialism is vital for understanding the social and cultural processes in the country. This research aims to analyze the life strategies and identities of ethnic minorities, exploring their interactions with society and state institutions from the perspectives of existentialism and contemporary social philosophy. The study is of significant academic importance as it contributes to a deeper understanding of the cultural and social dynamics in Kazakhstan’s multicultural environment. The practical significance of the work lies in developing suggestions for improving policies in integration and cultural adaptation. The research methodology includes qualitative methods such as interviews and analysis of social media content. These methods allow for an in-depth examination of the personal experiences of ethnic minorities and their interactions with societal structures. Key findings demonstrate that philosophical and existential aspects play a significant role in preserving identity and aiding social adaptation of ethnic minorities. The research underscores the need for deeper interaction between state structures and minorities to create an effective model of multicultural interaction. This study makes an important contribution to social sciences by expanding the understanding of mechanisms of social integration and cultural dynamics in Kazakhstan. The practical value of this work lies in the potential to use the results to adjust cultural and educational programs aimed at supporting multiculturalism and social harmony. Keywords: ethnic minorities, existentialism, multiculturalism, social integration, Kazakhstan.